Multicomponent synthesis of pyrano-pyrazolo-pyridones by a bimetallic cobalt-cadmium magnetic catalyst - Mahmood Kamali; Akbar Mobaraki; Zahra Shirpak (Scientific Reports)
Abstract A novel series of pyranopyrazolopyridone derivatives was synthesized via multicomponent reaction involving 4-hydroxy-6-methylpyridin-2-ones, aromatic aldehydes, and pyrazolone. To this end, a new high-efficiency bimetallic cobalt-cadmium heterogeneous magnetic catalyst was designed, synthesized, characterized, and used in this reaction. Instrumental techniques such as elemental analysis (CHN), EDX, SEM, TEM, FT-IR, XRD, VSM, and TGA were used to characterize the catalyst. To maximize efficiency, reaction conditions were optimized across all parameters, including temperature, time, and the amount of catalyst used. In the optimized reaction conditions, 78 °C and 10 h in the presence of 25 mol% of the catalyst, 73–94% isolated yields of pyranopyrazolopyridone derivatives were obtained in an ethanolic solution. Key advantages of this synthesis include operational simplicity, relatively short reaction time, use of an environmentally friendly heterogeneous bimetallic catalyst, and easy magnetic separation.